Predictors of self-management in patients with chronic low back pain - Banerjee, Anirban (2019)
Background: Self-management (SM) is a key strategy for managing chronic low back pain (CLBP) and defines how individuals manage their disease, symptoms, treatment and roles. However, no longitudinal study has examined the predictive relationships between SM and biopsychosocial outcome measures in patients with CLBP. This PhD thesis outlines the body of research that examined the predictive relationship between SM constructs and biopsychosocial outcome measures in patients with CLBP.